The Microstructure and Magnetoelectric Properties of Multiferroic Composites - Bartkowska, J A; Bochenek, D; Niemiec, P (Archives of metallurgy and materials, 2018)
Multiferroic composites are very promising materials because of their applicability because the magnetoelectric effect occurs in them. The subject of the study were two multiferroic ceramic composites: leaded obtained from powder of the composition PbFe0.5Nb0.5O3 and ferrite powder of the composition Ni0.64Zn0.36Fe2O4 and unleaded which was obtained from the powder of the composition BaFe0.5Nb0.5O3 and the same ferrite powder Ni0.64Zn0.36Fe2O4. For the both multiferroic materials the following studies were conducted: SEM, BSE, EDS, XRD and the temperature dependence of dielectric constant ε(T). Using the previously developed method of calculating the magnetoelectric coupling factor (g), based on dielectric measurements, the magnitude of the magnetoelectric effect in the multiferroic composites was determined.